Kinetic and Kinematic Assessment of Functional Tasks 1 Year after a Knee Injury—A Systematic Review - DeVecchis, Marina; Reed, Charlotte; Ladlow, Peter; Behan, Fearghal P.; McKay, Gordon; Bell, Vanessa; O'Sullivan, Oliver (International Journal of Sports Medicine, 2025)
Osteoarthritis (OA) is a common, multi-factorial and -aetiological condition, causing pain, disability and reduced function. Post-traumatic OA (PTOA) is more common in younger populations, especially after anterior cruciate ligament (ACL) or meniscal injury. Identifying those at increased risk of PTOA using molecular, imaging and biomechanical biomarkers is a research priority. This systematic review aims to identify functional tasks used to assess knee kinematics and kinetics at least a year from injury, describe any differences found between the injured and uninjured contralateral and control knees and identify associations with PTOA. Searches were performed on Medline, CINAHL and EMBASE, with reference lists reviewed. The initial search yielded 2504 studies, with six more detected from reference lists. Thirty-three studies involving 1251 participants (n=737 injured, all ACL, mean age 25.1, 49.9% male, 1–13 yr post-injury) were included. Studies included the following dynamic tasks: landing (n=25), jumping (n=3), cutting (n=5) or squatting (n=3). Overall, reductions in knee flexion and extension angles and moments, increased knee valgus and energy absorption were demonstrated in injured knees. However, this was inconsistent across studies, with data heterogeneity preventing direct comparison and meta-analysis. Changes in biomechanics are present from 1-year post-injury, persisting for several years; however, consensus regarding core outcome sets is required.
Keywords: Post-traumatic osteoarthritis; Kinetics; Kinematics; Biomechanics; PTOA